Storytelling tourist experiences in the websites of world heritage historical centers - Frias, Catarina (2019)
The objectives of this chapter are to: relate the concepts of world heritage sites, tourist experience and storytelling.To identify the dimensions of the pre-tourist storytelling experiences in world heritage centers in Portugal, based on the information provided in their official websites. To discuss the findings with world heritage historic centers management entities.